Vitimodogmática e limitação da responsabilidade penal nas ações arriscadas da vítima - Emeterio Silva de Oliveira Neto (2019)
The present thesis focuses on the purpose of structuring the victimodogmatic, that is, the criminal relevance of the victim's behavior, as a mechanism for imposing limits on the punitive power of the State, based on the plexus of fundamental rights and guarantees emanating from the constitutional legal order. That means, in other words, that punishment is not an end in itself, but must be seen, in reverse, as the last means of achieving social peace, so greatly desired by criminal law, in democratic societies. In this sense, studies developed in the field of victimology, in its modern version, reveal that, in countless situations, the interests of the individuals involved in the criminal act, as well as those of the community to which they belong, are satisfied to a greater extent through autocompositional methods, in comparison to the prison sentence for the offender. On the other hand, as initially clarified, it matters to the dogmatics of the theory of crime to assess, with due caution, the situations in which the victim contributes to the occurrence of the prima facie criminal fact, and thus, having a fair distribution of criminal liability for the offender or, when appropriate, to avoid the punishment, for considering the crime non-existent. In such a scenario, two victimodogmatics trends emerge: for the first and majoritarian one, the victim's behavior will benefit the agent only at the time of the penalty deliberation, while the second argues that, on certain occasions, this behavior may lead to the exclusion of the typicality of the conduct. By providing a detailed dogmatic analysis of the victim's coefficient of behavior, the victimodogmatics, through its categories (eg, self-placement at risk and victimological principle), focuses on typicality, one of the constitutive elements of crime, relying, therefore, on the contributions of the objective criminal imputation theory. In view of these considerations, it is sought, under the limits of the constitutional principle of self-responsibility, to change the paradigm according to which the subject named as a victim is always innocent and the one appointed as the author is always guilty as charged, which will always be criminal, thus, forgetting other factors, purposely outlined throughout this research. The viability of the victimodogmatic instruments brought in is tested in the light of several penal types, most of them foreseen in the Brazilian legislation, as well as through the analysis of emblematic cases. The work is of bibliographical nature; nonetheless, there is the appreciation of important decisions issued by national and foreign courts.